Academic Information Systems and Recommendations using AHP at SMA Islamic Center Tangerang - Alvira Putri Yudini; Calandra Alencia Haryani; Andree E. Widjaja; Hery Hery; Suryasari Suryasari (Ultimatics : Jurnal Teknik Informatika, 2021)
Nowadays, technology is indispensable to solve problems. Technology can facilitate communication without thinking about distance, space, and time. Currently, the advancement of technology is useful for most people in carrying out their activities, especially in the field of education. Islamic Centre High School Tangerang is one of the schools that require information systems to manage data as it still uses the manual method. This research was specifically conducted to assist t Islamic Centre High School Tangerang in building a system for managing school data, so that it can provide recommendations to students to decide on a study program to a higher level of education, as well as to help parents monitoring their children activities. The methodology used in this study is qualitative methods, RAD methodology and the Prototyping method. Meanwhile, the method of recommending study programs for students used the Analytical Hierarchy Process method, that is by comparing the value of criteria consisting of accreditation, majors, grades, and comparison of alternative values consisting of study programs and universities. The system was tested using black box testing method. The result of this study is a web-based academic information systems with recommendation feature. The system can display a ranking of student study program recommendations based on a comparison of criteria and alternative values using the Analytical Hierarchy Process Method